The Fulcrum of the Human Heart (Cardiac fulcrum) - Trainini, Jorge Carlos; Wernicke, Mario; Beraudo, Mario; Trainini, Alejandro (Journal of Cardiology and Cardiovascular Medicine, 2024)
Introduction: The functional anatomy of the myocardium allows envisioning that it initiates and ends at the origin of the great vessels. In our research, we have always considered that it should have a point of attachment to allow its helical rotation to fulfill the fundamental movements of shortening-torsion (systole) and lengthening-detorsion (suction), which once found, was called the cardiac fulcrum. Materials and methods: A total of 31 hearts, arising from the morgue and slaughterhouse were used: 17 corresponded to bovids and 14 were human. Anatomical and histological studies were performed. The heart was fixed in 10% buffered formalin. Hematoxylin-eosin, Masson’s trichrome staining technique, and 4-micron sections were used for the histological study, and 10 % formalin was used as a buffer. Results: The anatomical investigations have revealed that all the hearts (bovids and humans) have myocardial support whose histological structure in the analyzed specimens presents with an osseous or chondroid-tendinous character. In this structure, which we have called the cardiac fulcrum, are inserted the myocardial fibers at the origin and end of the band, which correspond to the continuous myocardium coiled as a helix. Conclusion: This description of the fulcrum would end the problem of lack of support of the myocardium to fulfill its function of suction/ejection.